A new nonisolated soft switched DC-DC bidirectional converter with high conversion ratio. Issue 12 (1st December 2020) - Vesali, Mahmood; Delshad, Majid; Adib, Ehsan; Amini, Mohammad Reza
ABSTRACT: In this paper, a new soft switching bidirectional DC-DC converter with high conversion ratio is proposed. In the proposed converter, soft switching condition is provided with only one auxiliary switch for both directions, which simplifies the structure of the converter. The switching in boost mode is under ZCS condition and in buck mode is under ZVS condition. In the proposed converter, all diodes turn off under ZCS condition; therefore, losses related to diodes reverse recovery are eliminated. The control of the auxiliary switch is complementary to the main switch; thus, complex control circuit is not required. The voltage stress of the switch in boost mode is reduced extremely due to high voltage gain. The proposed converter is analysed, and to confirm the theoretical analysis, a 200-W prototype is implemented and the results are presented. Consequently, the efficiency of the proposed converter at full load is 97.5%.